The days i loved you most ebook A novel. - Neff, Amy (2024)
INTERNATIONAL BESTSELLER A Today Show Pick "I've never read a story quite like this deeply moving, complex novel." —Jodi Picoult, #1 New York Times bestselling author Unforgettable and utterly romantic, The Days I Loved You Most is an emotional, life-affirming novel that asks, What if you could write the final chapter of your own love story? In the summer of 1941, on the New England shores where they were raised, Evelyn and Joseph fell in love. Now, more than sixty years later, with a lifetime between them, they have gathered their three grown children to share the staggering news: she has received a heartbreaking diagnosis, and he can't live without her. So in one year's time they will end their love story on their own terms. Over the next year, the couple retraces their past—all the joys and regrets that brought them to this moment. They embark on a journey to live out their greatest dreams and to connect with each of their children. But as their final days draw closer, they must confront the stark reality of what's to come, and make peace with the legacy they will leave behind for their family. Spanning the twentieth century from World War II to 9/11 and beyond, The Days I Loved You Most is a timeless tale of unwavering devotion — a moving tribute to the enduring power of love and a reminder that even in the darkest moments, there is always hope and beauty to be found.